The hidden Cézanne : from sketchbook to canvas - Haldemann, Anita; Cézanne, Paul, 1839-1906.; Öffentliche Kunstsammlung Basel (Munich : Prestel, 2017)
One of the founding artists of modern art, Paul Cézanne (1839-1906) is now widely acclaimed as the preeminent painter of the late nineteenth century. Less well known is his groundbreaking work as a draftsman; relatively little scholarship has been devoted to this aspect of his oeuvre, which is rarely presented in exhibitions. The Kunstmuseum Basel's Kupferstichkabinett (Department of Prints and Drawings) contains 154 sheets by Cézanne, making it the most comprehensive and significant collection of the artist's drawings in the world. The collection dates back to the 1930s, attesting to the museum's farsighted collection policy. Two thirds of these drawings come from dissolved sketchbooks, which were reconstructed in view of this presentation. The starting point and nucleus of Cézanne's creative thinking, they allow us to observe Cézanne's everyday practice as a draftsman up close. Early scenes of violence appear side by side with portrait sketches; copies after Delacroix or ancient sculptures alternate with landscapes and bathers. Repetition and slight variation of the angle from which he studied a motif enabled the artist to understand how perceptions formed and to develop entirely new pictorial registers. In his watercolors, Cézanne explored the dynamic interplay between line and color, casting off the constraints of the tradition. In his paintings, too, the line is vital. He often produced a preparatory drawing on the canvas and reworked it with the brush before executing the picture in paint. This book offers fascinating insights into this outstanding painter's creative process. Exhibition: Kunstmuseum Basel - Neubau, Switzerland (10.06.-24.09.2017).
Catalog of an exhibition held at Kunstmuseum Basel, Neubau, Switzerland, June 10-September 24, 2017.
Imported from: zcat.oclc.org:210/OLUCWorldCat (Do not remove)
boek
Keywords: Cézanne, Paul, -- 1839-1906 -- Exhibitions; Cézanne, Paul, -- 1839-1906.; Exhibition catalogs